Co-creating a social science research agenda for Long Covid - Cousins, Oonagh; Jokela-Pansini, Maaret; Alwan, Nisreen A.; Barnard, Ella; Dainow, Jo; Dalton, Caroline; Davies, Gail; Faghy, Mark A.; Gilmour, Eileen; Patel, Ian; Sherwood, Ondine; Westerhof, Lotus; et al. (Frontiers in Public Health, 2025)
IntroductionOur objective was to understand how social scientific research could best address the needs and concerns of patients, families, carers, healthcare professionals, academics, private and public sector professionals, and volunteers from Long Covid charities and support groups and people with lived experience of Long Covid. We worked with different stakeholders to develop a list of research priorities that particularly focused on social science as this is where our collective expertise lies, but similar methods could also be used to set research priorities in the natural sciences, medicine or the humanities.MethodsWe used purposive sampling and conducted two online surveys. The first online survey (N = 57) asked participants to identify their top five questions of concern, which resulted in a list of 253 questions. These questions were then consolidated, refined and edited down to 55 questions, categorized by topic. In the second survey (N = 66), we asked participants to select and rank their top 10 questions from this refined list. The final output was a ranked list of nine questions based on those prioritized by at least 50% of the respondents.ResultsNine research questions were developed concerning (i) treatments, therapies, and strategies; (ii) financial support; (iii) repeated reinfections; (iv) training of healthcare professionals; (v) mental health impact; (vi) future of research funding; (vii) airborne transmissions of COVID-19; (viii) developing therapeutics informed by patients’ experiences; and (ix) socioeconomic impacts of Long Covid. Many of the issues raised mirror those discussed in previous work in the UK and internationally, but additional novel themes emerged, underscoring the value of this collaborative approach.ConclusionOur survey revealed the value of including the voices of diverse individuals affected by Long Covid and those working in this area and highlighted priorities for social science in the field of Long Covid research.